Australia: Country Report on Human Rights - Corrin, Jennifer (Victoria University of Wellington Law Review, 2009)
This article provides a country report on the status of human rights in Australia. Human rights law in Australia is embodied in three sources: constitutional provisions, federal, state and territorial legislation, and the common law. However, the author notes that Australia has not embraced the 'rights revolution' seen elsewhere around the world as it does not have a constitutionally enshrined charter of human rights. This status of human rights under Australian law reflects the nation's conservative approach to constitutional law reform, and it is argued that the above sources of human rights law do not provide a comprehensive regime for the protection of human rights in Australia. However, several states have proved that popular support for human rights protection is a political possibility, which shows cautious optimism for the future of human rights laws in Australia.